2005
DOI: 10.1186/1476-511x-4-18
|View full text |Cite
|
Sign up to set email alerts
|

Serum butyrylcholinesterase in type 2 diabetes mellitus: a biochemical and bioinformatics approach

Abstract: Background: Butyrylcholinesterase is an enzyme that may serve as a marker of metabolic syndrome. We (a) measured its level in persons with diabetes mellitus, (b) constructed a family tree of the enzyme using nucleotide sequences downloaded from NCBI. Butyrylcholinesterase was estimated colorimetrically using a commercially available kit (Randox Lab, UK). Phylogenetic trees were constructed by distance method (Fitch and Margoliash method) and by maximum parsimony method.Results: There was a negative correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…ACE from the electric eel and BCE from equine serum were used as enzymes. The enzyme BCE from equine serum shows high homology with human BCE; it was estimated that the rate of evolution for this enzyme was about 2.2 million years for 1% amino acid change . The ACE from the electric eel shows high homology with human nerve system ACE subtype.…”
Section: Resultsmentioning
confidence: 99%
“…ACE from the electric eel and BCE from equine serum were used as enzymes. The enzyme BCE from equine serum shows high homology with human BCE; it was estimated that the rate of evolution for this enzyme was about 2.2 million years for 1% amino acid change . The ACE from the electric eel shows high homology with human nerve system ACE subtype.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that BuChE may be indirectly contributing to the pathogenesis of T2DM by causing insulin resistance [36]. In fact, a locus on chromosome 3q27, which is near the chromosomal locus of BuChE (3q26), has been linked to T2DM in a French population in one study [37].…”
Section: Role Of Ache and Buche In The Pathogenesis Of T2dmmentioning
confidence: 99%
“…In the same vein, in addition to its role in cholinergic neurotransmission, acetylcholine exerts a potential anti-in ammatory e ect mediated by "cholinergic anti-in ammatory re ex" (5). Accordingly, a positive correlation of the blood serum level of acetylcholinesterase, butyrylcholinesterase and C-reactive protein (CRP) was reported in obese and diabetic patients (6)(7)(8)(9)(10).…”
mentioning
confidence: 99%